Uso da ventilação não invasiva após a extubação: revisão da literatura - Lidiane Ferreira dos Santos (2012)
The Respiratory failure after extubation occurs even in patients with an appropriate indication and driving weaning. About 13% to 19% of patients extubated require reintubation. They have seven times higher mortality than those successfully extubated. The non-invasive mechanical ventilation has been used routinely in patients who develop acute respiratory failure after extubation, although the scientific evidence for this indication still controversial. Objective: Demonstrate the use of noninvasive ventilation as prevention of reintubation in patients with Chronic Obstructive Pulmonary Disease and Acute Respiratory Failure after extubation. Conclusion: This study showed that there are still conflicting results regarding the application of NIV for respiratory failure after extubation, underscoring the need for more consistent evidence for this indication. In relation to respiratory failure secondary to COPD or IRPC is no convincing evidence for its use, recommendation grade "A" in the III Brazilian Consensus Conference on Mechanical Ventilation.